Arithmetic progression (a.p.), Mathematics

A series is said to be in Arithmetic Progression (A.P.) if the consecutive numbers in the series differs by a constant value. This constant value is referred to as "common difference". The series in which the consecutive terms increases by a constant quantity, is referred to as an increasing series and if the terms decrease by a constant quantity it is referred to as a decreasing series. The series

                            3, 7, 11, 15, 19, .............

is an example of increasing series, while the one like

                            8, 2, -4, .........

is an example of decreasing series.

In an A.P. the first number is denoted by "a" and the common difference is denoted by "d". If we know the values of a and d, it is quite easy to get the terms of the Arithmetic Progression. In terms of a and d, the consecutive terms of arithmetic progression are

                   a, a + d, a + 2d, a + 3d, ......... a + nd

We observe that the first term is a, the second term is a + d, the third term being a + 2d. The point to note is that for the first term the coefficient of d is zero, for the second term it is one and for the third term it is 2. By observing this pattern can we conclude that the coefficient of nth term is n - 1? Yes, we can. In fact, the nth term is given by

                    Tn  = a + (n - 1)d

Generally the Tn  which is the last term is also denoted by "l" (small alphabet 'l'). That is, l = a + (n - 1)d.

Now let us look at an example.

Example 

If the first term of an A.P. 'a' = 3 and the common difference 'd' = 2, what are the first five terms of the series and what would be the nth term? They are calculated as follows. We know that

                   T1     = a                = 3

                   T2     = a + d           = 3 + 2 = 5

                   T3     = a + 2d         = 3 + 2(2) = 7

                   T4     = a + 3d         = 3 + 3(2) = 9

                   T5     = a + 4d         = 3 + 4(2) = 11

                   :                                          :
                   :                                          :

           l = Tn        = a + (n - 1)d  = 3 + (n - 1)(2)

                                                = 3 + 2n - 2

                                                = 2n + 1

Posted Date: 9/13/2012 4:18:07 AM | Location : United States







Related Discussions:- Arithmetic progression (a.p.), Assignment Help, Ask Question on Arithmetic progression (a.p.), Get Answer, Expert's Help, Arithmetic progression (a.p.) Discussions

Write discussion on Arithmetic progression (a.p.)
Your posts are moderated
Related Questions


1. Consider the following differential equation with initial conditions: t 2 x'' + 5 t x' + 3 x = 0, x(1) = 3, x'(1) = -13. Assume there is a solution of the form: x (t) = t

y'' + 2y = 2 - e-4t, y(0) = 1 use euler''s method with a step size of 0.2 to find and approximate values of y

#question.help.

Substitution Rule for Definite Integrals Now we need to go back and revisit the substitution rule as it also applies to definite integrals.  At some level there actually isn't

Draw the direction field for the subsequent differential equation. Draw the set of integral curves for this differential equation.   Solution:  y′ = y - x  To draw direct

Absolute Convergence While we first talked about series convergence we in brief mentioned a stronger type of convergence but did not do anything with it as we didn't have any

Michael scored 260 points during his junior year on the school basketball team. He scored 20% more points during his senior year. How many points did he score during his senior yea

i need somehelp i am not the sharpest in the pack so plz help me thank you i hope you do